Analisis Keterampilan Berpikir Kreatif Siswa menggunakan Model Pembelajaran STEM pada Siswa Kelas V SDN 001 Salo - Novi Sagita Arianti; Purwono Purwono (Universitas Negeri Makassar, 2020)
This study aims to describe students' creative thinking skills using science, technology, engineering, mathematics learning models for elementary school students. The research method used is descriptive qualitative research method, with preparatory steps, field work, and data analysis. Sources of data are all students of class V SDN 001 Salo totaling 21 students, consisting of 7 male students and 14 female students. Data collection techniques used are observation, interviews, and documentation. The research instruments used were student observation sheets and teacher interview guidelines. The data analysis technique was carried out using qualitative data analysis techniques. The results showed that students' creative thinking skills were at a moderate level. The teacher knows the learning models of science, technology, engineering, mathematics but is not skilled in its implementation. The conclusion of this study is that students' creative thinking skills are classified as moderate because teachers are less skilled in applying science, technology, engineering, mathematics learning models in their learning. Teacher training and assistance is needed so that they can apply the science, technology, engineering, mathematics learning models which are believed to be able to improve the creative thinking skills of elementary school students.